2014
DOI: 10.4172/2161-1122.1000240
|View full text |Cite
|
Sign up to set email alerts
|

ANB, Wits And Molar Relationship, Do They Correlate In Orthodontic Patients?

Abstract: Objective:To determine the association between the anteroposterior relationship of the dental arch and the jawbase in a random sample of orthodontic patients. Materials and Methods: 478 pretreatment lateral cephalometric radiographs and study models were evaluated. Cephalometric analysis using Dolphin software to measure the ANB angle and Wits appraisal was performed, and Angle's classification was evaluated. Results:The agreement of the sagittal classification of the dental arch was higher with the anteropost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
3
0
3
Order By: Relevance
“…In the study of Aldrees AM. et al 18 the correlation between the dental relation of the molars and the ANB angle was 57.7%, while in the study of Zhou L. et al 19 the correlation was 61%. The difference is explained with the age of the patients who were included in both studies, i.e., the presence of patients with early permanent dentition where the molars are still in the tubertuber position before their transition to Class I.…”
Section: Resultsmentioning
confidence: 91%
“…In the study of Aldrees AM. et al 18 the correlation between the dental relation of the molars and the ANB angle was 57.7%, while in the study of Zhou L. et al 19 the correlation was 61%. The difference is explained with the age of the patients who were included in both studies, i.e., the presence of patients with early permanent dentition where the molars are still in the tubertuber position before their transition to Class I.…”
Section: Resultsmentioning
confidence: 91%
“…16 El análisis el ángulo ANB es una medida angular que se usa para describir la discrepancia esquelética entre el maxilar y la mandíbula en sentido anteroposterior. 17 Jacobson advierte que el ángulo ANB no señalaba una evaluación adecuada debido a que la mandíbula tendía a crecer y rotar. La posición anteroposterior del nasion puede afectar la relación con el punto A y B que incide sobre el ángulo ANB, por eso se sugirió una alternativa que fue la valoración Wits.…”
Section: Factores Que Inciden En La Determinación Del áNgulo Anb Y Va...unclassified
“…La posición anteroposterior del nasion puede afectar la relación con el punto A y B que incide sobre el ángulo ANB, por eso se sugirió una alternativa que fue la valoración Wits. 17 Los siguientes factores afectan la determinación del ángulo ANB:…”
Section: Factores Que Inciden En La Determinación Del áNgulo Anb Y Va...unclassified
See 1 more Smart Citation
“…In other words, a person presenting with Class I malocclusion on Angle's classification may have a Class II or Class III skeletal pattern and vice versa. However, another study also reported a similar percentage of 57% (5). Therefore, when performing prevalence studies of malocclusion types in a region or population, it is important to distinguish how the classification is done and which type of malocclusion is being reported.…”
Section: Introductionmentioning
confidence: 97%